Public Interest in Private Law Relations of Transition Democracies: A Modern View from the Standpoint of a Systemic Approach - Berestova, Iryna E.; Verenkiotova, Olha V.; Serbina, Natalii? O.; Seminoh, Svitlana V. (International Journal of Criminology and Sociology, 2021)
The study investigates the legal nature of the category of "public interest" in private law relations from the standpoint of a systematic scientific approach to law in the countries of post-Soviet society in the modern period. The study states the affiliation of public and private law to the means of achieving the purpose of the law: the recognition of a person, their rights and freedoms as the highest social value of the state. The unsuitability of the theory of the branch belonging to public law has been proved using the universal criterion of separation: the use of the category of "public interest" in the development of the subject and method of the branch in private legal relations. It is concluded that the division of law into private and public is inconsistent in terms of their differentiation of the criterion "method of protecting the rights of their participants", which is activated only after the violation of the latter, while subjective law also exists before the violation, during the existence of regulatory legal relations, and it is the subjective law that forms the affiliation to the relevant industry. During the study, signs of public interest as a legal category were formed. In addition, modern features of public interest as a legal category were outlined from the standpoint of a systematic approach: the general nature of public interests; connectedness with large-scale involvement; recognition by the state and the provision of the law; the possibility of their implementation through measures of state power.